2019
DOI: 10.3889/oamjms.2019.320
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Cryptococcal Abscess in HIV-Negative Patient: A Case Report and Literature Review

Abstract: BACKGROUND: Cryptococcus is a common cause of opportunistic infection in HIV-positive patients. While the incidence of this disease has decreased in AIDS-associated cases, cryptococcal infection in immune-competent person has been increased. CASE PRESENTATION: We report a case of cryptococcosis and literature review of pathogenesis and clinical aspects of cryptococcal central nervous system infection. A 64-year-old man, from Flores, complaining of severe headache since a few days before admitted to hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The rst case of cryptococcal brain abscesse was reported by Gorden et al in 1985 in New Orleans [8]. Taking the overview of the reported cases so far, we found that males are slightly more prevalent than females; The abscesses can locate in various parts of the brain parenchyma, mostly exhibited as single lesion; The most common symptoms were headaches; Onset time varies from days to months; Surgical resection is crucial for disease diagnosis and treatment; Patient may beni t from antifungal therapy but speci c treatment options are yet to be explored [6, [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The rst case of cryptococcal brain abscesse was reported by Gorden et al in 1985 in New Orleans [8]. Taking the overview of the reported cases so far, we found that males are slightly more prevalent than females; The abscesses can locate in various parts of the brain parenchyma, mostly exhibited as single lesion; The most common symptoms were headaches; Onset time varies from days to months; Surgical resection is crucial for disease diagnosis and treatment; Patient may beni t from antifungal therapy but speci c treatment options are yet to be explored [6, [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…One report suggested a mortality rate of 81.2%, with most deaths directly attributable to cryptococcal infection and with over half of deaths occurring within 2 weeks after diagnosis [4]. Cryptococcal infection and abscess formation can affect almost any part of the body, with reports of bone, skin, intramuscular, cerebellar, brain stem, retropharyngeal, prostatic, ocular, breast, thyroid, ovarian, and mediastinal abscesses seen in the literature [16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few cases of Cryptococcus Laurentii causing human infection were reported in literature. Cryptococcal infections are mostly seen in immunocompromised patients, particularly those with cellular immune defects including advanced HIV infection with predilection of central nervous system [1][2][3][4]. The clinical presentation is usually subtle, vague, and indolent over a period of one to two weeks.…”
Section: Introductionmentioning
confidence: 99%